Ottolenghi test kitchen shelf love : recipes to unlock the secrets of your pantry, fridge, and freezer - Murad, Noor; Ottolenghi, Yotam (Clarkson Potter, 2021)
"From the New York Times bestselling author and his superteam of chefs, this is Ottolenghi, unplugged: 86 irresistible recipes for relaxed, flexible home cooking that will bring the love to every shelf in your pantry, fridge, and freezer. Led by Yotam Ottolenghi and Noor Murad, the revered team of chefs at the Ottolenghi Test Kitchen gives everyday home cooks the accessible yet innovative Middle Eastern-inspired recipes they need to put dinner on the table with less stress and less fuss. With fit-for-real-life chapters like "The Freezer Is Your Friend," "That One Shelf in the Back of Your Pantry," and "Who Does the Dishes?" (a.k.a. One-Pot Meals), Shelf Love teaches readers how to flex with fewer ingredients, get creative with their pantry staples, and add playful twists to familiar classics. All the signature Ottolenghi touches fans love are here--big flavors, veggie-forward appeal, diverse influences--but are distilled to maximize ease and creative versatility. These dishes pack all the punch and edge you expect from Ottolenghi, using what you've got to hand--that last can of chickpeas or bag of frozen peas--without extra trips to the grocery store. Humble ingredients and crowd-pleasing recipes abound, including All-the-Herbs Dumplings with Caramelized Onions, Mac and Cheese with Za'atar Pesto, Cacio e Pepe Chickpeas, and Crispy Spaghetti and Chicken"--